Interleukin-23-Mediated Inflammation in Pseudomonas aeruginosa Pulmonary Infection - Dubin, Patricia J. (American Society for Microbiology, 2012)
Pseudomonas aeruginosa is an opportunistic pathogen that is capable of causing acute and chronic pulmonary infection in the immunocompromised host. In the case of cystic fibrosis (CF), chronic P. aeruginosa infection causes increased mortality by promoting overly exuberant airway inflammation and cumulative lung damage. Identifying the key regulators of this inflammation may lead to the development of new therapies that improve P. aeruginosa-related mortality. We report here that interleukin-23 (IL-23), the cytokine most clearly tied to IL-17-mediated inflammation, also promotes IL-17-independent inflammation during P. aeruginosa pulmonary infection. During the early innate immune response, prior to IL-17 induction, IL-23 acts synergistically with IL-1β to promote early neutrophil (polymorphonuclear leukocyte [PMN]) recruitment. However, at later time points, IL-23 also promoted IL-17 production by lung γδ T cells, which was greatly augmented in the presence of IL-1β. These studies show that IL-23 controls two independent phases of neutrophil recruitment in response to P. aeruginosa infection: early PMN emigration that is IL-17 independent and later PMN emigration regulated by IL-17.